The Study of Tuff Breccia for Batik Wasterwater Treatment Media in Bayat, Klaten District, Central Java - Wawan Budianta; Johan Syafri Mahathir Ahmad; I Wayan Warmada (Universitas Insan Cendekia Mandiri, 2023)
Batik wastewater produced in the batik industry in Bayat, Klaten Regency, contains chromium and phenol, which pass the wastewater quality standard. This study aimed to evaluate the ability of tuff breccia from the study area to reduce chromium and phenol concentration in batik wastewater. Mineralogical and chemical characterization was conducted to investigate tuff breccia's mineralogical and chemical composition. A batch and regeneration test was conducted to investigate tuff breccia's ability to reduce the chromium and phenol concentration in the batik wastewater. The characterization of tuff breccia indicates that the tuff breccia consists of fragments, minerals (quartz, plagioclase), and clay minerals (smectite and illite). The batch test results show that the grain size of tuff breccia and the pH value significantly influence the ability of tuff breccia to reduce the chromium and phenol concentration in batik wastewater. The regeneration test showed that the tuff breccia would decrease the capability by up to 30 percent after five times of use.